2006
DOI: 10.1111/j.1399-3038.2006.00443.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and immunologic effects of sublingual immunotherapy in asthmatic children sensitized to mites: a double‐blind, randomized, placebo‐controlled study

Abstract: Immunotherapy through oral routes is thought to be a valuable therapeutic option for asthma. The clinical and immunologic effects of sublingual immunotherapy (SLIT) in children with asthma caused by mites were evaluated in a double-blind, placebo-controlled study for 6 months. Patients (aged 6-12 yr) with mild-to-moderate asthma, with single sensitization to mite allergen, received either SLIT or placebo with a standardized Dermatophagoides pteronyssinus (D.p.)/D. farinae (D.f.) 50/50 extract. The cumulative d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
1
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(96 citation statements)
references
References 19 publications
4
88
1
3
Order By: Relevance
“…In HDM-sensitive children with mild to moderate asthma, it has been demonstrated that SLIT for 6 months was associated with a decrease in asthma symptoms and medication use, as well as with an improvement in lung function [166,167]; however, in children with asthma optimally controlled by pharmacologic treatment and HDM avoidance, SLIT-tablets did not provide additional benefit, despite a significant reduction in allergic response to HDM [168]. Retrospective studies in this pediatric population indicate that HDM-based SLIT significantly reduces the number of acute asthma attacks [169], the duration and dose of ICS [170], and symptomatic medication use [171].…”
Section: Pediatric Populationsmentioning
confidence: 99%
“…In HDM-sensitive children with mild to moderate asthma, it has been demonstrated that SLIT for 6 months was associated with a decrease in asthma symptoms and medication use, as well as with an improvement in lung function [166,167]; however, in children with asthma optimally controlled by pharmacologic treatment and HDM avoidance, SLIT-tablets did not provide additional benefit, despite a significant reduction in allergic response to HDM [168]. Retrospective studies in this pediatric population indicate that HDM-based SLIT significantly reduces the number of acute asthma attacks [169], the duration and dose of ICS [170], and symptomatic medication use [171].…”
Section: Pediatric Populationsmentioning
confidence: 99%
“…[22][23][24][25][26][27][28][29]32,33,[35][36][37] Six studies evaluated dust mite allergen. [22][23][24][25][26]32 The placebo-controlled studies demonstrated significant reductions in medication use in the SLIT group relative to the placebo group, with moderate to strong magnitudes of effect in patients with asthma and/or rhinitis. The magnitudes of effect could not be determined in 7 studies.…”
Section: Medication Scoresmentioning
confidence: 99%
“…[22][23][24][32][33][34][35]37,38 Seven studies evaluated dust mite allergen. [22][23][24][32][33][34]38 The SLIT-treated children in the placebo-controlled studies demonstrated moderate to strong improvement in asthma symptoms. The risk of bias was low in 3 studies.…”
Section: Asthmamentioning
confidence: 99%
“…On the contrary, other works underlined the capability of SLIT with pollen allergens or with house dust mites to induce an increase of specific IgG4 (36)(37)(38)(39). Despite the lack of unanimous consent regarding the mechanism of action of SLIT, several trials have shown the efficacy of SLIT in improving symptoms in patients with allergic rhinitis and/or bronchial asthma, and with latex allergy.…”
Section: Discussionmentioning
confidence: 99%